Therapeutic Potential of Electromyostimulation (EMS) in Critically Ill Patients—A Systematic Review - Balke, Maryam; Teschler, Marc; Schäfer, Hendrik; Pape, Pantea; Mooren, Frank C.; Schmitz, Boris (Frontiers in Physiology, 2022)
Ample evidence exists that intensive care unit (ICU) treatment and invasive ventilation induce a transient or permanent decline in muscle mass and function. The functional deficit is often called ICU-acquired weakness with critical illness polyneuropathy (CIP) and/ or myopathy (CIM) being the major underlying causes. Histopathological studies in ICU patients indicate loss of myosin filaments, muscle fiber necrosis, atrophy of both muscle fiber types as well as axonal degeneration. Besides medical prevention of risk factors such as sepsis, hyperglycemia and pneumonia, treatment is limited to early passive and active mobilization and one third of CIP/ CIM patients discharged from ICU never regain their pre-hospitalization constitution. Electromyostimulation (EMS) is known to improve strength and function of healthy and already atrophied muscle, and may increase muscle blood flow and induce angiogenesis as well as beneficial systemic vascular adaptations. This systematic review aimed to investigate evidence from randomized controlled trails (RCTs) on the efficacy of EMS to improve the condition of critically ill patients treated on ICU. A systematic search of the literature was conducted using PubMed (Medline), CENTRAL (including Embase and CINAHL), and Google Scholar. Out of 1,917 identified records, 26 articles (1,312 patients) fulfilled the eligibility criteria of investigating at least one functional measure including muscle function, functional independence, or weaning outcomes using a RCT design in critically ill ICU patients. A qualitative approach was used, and results were structured by A) stimulated muscles/ muscle area (quadriceps muscle only; 2-4 leg muscle groups; legs and arms; chest and abdomen) and B) treatment duration (≤10 days, >10 days). Stimulation parameters (impulse frequency, pulse width, intensity, duty cycle) were also collected and the net EMS treatment time was calculated. A high grade of heterogeneity between studies was detected with major cofactors being the analyzed patient group and selected outcome variable. The overall efficacy of EMS was inconclusive and neither treatment duration, stimulation site or net EMS treatment time had clear effects on study outcomes. Based on our findings, we provide practical recommendations and suggestions for future studies investigating the therapeutic efficacy of EMS in critically ill patients.